2004
DOI: 10.1016/j.bpc.2003.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 2,2,2-trifluoroethanol with proteins: calorimetric, densimetric and surface tension approach

Abstract: The thermal denaturation of hen egg-white lysozyme was studied in the presence of 2,2,2-trifluoroethanol (TFE) at various pH values using micro differential scanning calorimetry. Quantitative thermodynamic parameters accompanying the thermal transitions were evaluated. It is observed that thermal unfolding of lysozyme in the presence of TFE upto a concentration of 4.0 mol dm follows a two-state denaturation mechanism as indicated by the equality y3 of van't Hoff and calorimetric enthalpies. The finer details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Recently it has been proposed that TFE acts by selectively desolvating the peptide backbone groups of the helix and thereby inducing the helical state. 46 Based upon calorimetric, densimetric, and surface tension measurements, we have suggested that TFE-protein interaction 47 includes a combination of both solvent-mediated effects and direct binding. The ITC results in the present studies ( Figures 8 and supplement 2) show that the heat liberated at each injection is nearly zero and the overall ITC profile does not indicate a significant binding pattern.…”
Section: Mode Of Interaction Of Tfe With Bsamentioning
confidence: 99%
“…Recently it has been proposed that TFE acts by selectively desolvating the peptide backbone groups of the helix and thereby inducing the helical state. 46 Based upon calorimetric, densimetric, and surface tension measurements, we have suggested that TFE-protein interaction 47 includes a combination of both solvent-mediated effects and direct binding. The ITC results in the present studies ( Figures 8 and supplement 2) show that the heat liberated at each injection is nearly zero and the overall ITC profile does not indicate a significant binding pattern.…”
Section: Mode Of Interaction Of Tfe With Bsamentioning
confidence: 99%
“…In solution #2, the protein's native structure is partially altered due to the good solvating properties of the TFE, and the protein chains are stabilized in a so-called partially-unfolded state, as described elsewhere [29][30][31]. Additionally, the TFE prevents inter-molecular interactions between the partially-unfolded protein coils, preventing the formation of an organized lattice in this solution and resulting in a Newtonian flow behavior.…”
Section: Shear Rheologymentioning
confidence: 99%
“…Most prominently, at high TFE concentrations, the interactions of the protein hydrophilic regimes with water molecules as well as the associated hydrophobic interactions within the protein are disrupted by TFE [27,[37][38][39]. The bulk effect causes unfolding of the tertiary structure of the proteins while concurrently strengthening some intra-molecular hydrogen bonds involved with secondary structures, such as˛-helixes.…”
Section: Resultsmentioning
confidence: 97%